PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY, NET PROFIT MARGIN, CURRENT RATIODAN DIVIDENT PAYOUT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA - Dyah Permatasari, 12.05.51.0110; Parmono Hadi, Teguh (Students' Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of DER, ROE, NPM, CR and DPR on Stock Prices in industry manufacturing company is go public in Indonesian Stock Exchange. The research wasconducted again because that empirical evidence were linked with fundamental factors with stock prices still showed the different results that need further research to prove how the influence of fundamental factor on stock prices especially the industry manufacturing sector in Indonesian Stock Exchange. This study was taken because there are still differences between the research study with each other.This research was conducted using secondary data. Population in this research was industry manufacturing company obtained from share which was listed and “go public” in Indonesian Stock Exchage period 2012-2014. Sampling technique used was purposive sampling. There is 132 companies that can be analysed. This study is analyzed by using multiple regression. The multiple regression shows that ROE and CR have positive and significant impact on stock prices , DER has negative and significant effect on stock prices, DPR have positive and not significant impact on stock prices and NPM has negative and not sigifikan impacton stock prices . Adjusted R Square is 0,353 this means 35.3% of the dependent variable can be explained by the independent variable , while the remaining 64.7 % is explained by other causes outside the model Keywords: Stock Price, Debt to Equity Ratio, Return On Equity, Net Profit Margin,Current Ratio and Divident Payout Ratio.